Povezovanje lastnikov gozdov kot ukrep za povečanje konkurenčnosti v zasebnih gozdovih ob uvajanju sodobnih tehnologij - Pezdevšek Malovrh, Špela (Gozdarski vestnik, 2006)
Slovenian forest owners lack the sufficient organisation and cooperation in managing their forests. One of the consequences is poorer competitiveness of the private forestry sector. In order to increase the competitiveness of private forest management and the use of new technologies it is necessary to enhance various forms of private forest owners' association. Our survey shows that forest owners are aware of the problem of weak cooperation. Part of this problem is lack of appropriate motivation.
Keywords: zasebni gozdovi; gospodarjenje z gozdovi